The Implementation of Project-Based-Learning Learning Model in Procedure Text Material of English Subject in Grade 11 Senior High School 1 Mojokerto City - Muhamad Nur Ilmiawan; Adelia Eka Mariska; Wiwik Mardiana; Adri Nirmala (Universitas Maritim AMNI Semarang, 2024)
This study aims to explore the application of Project-Based Learning (PjBL) learning model on procedure text material in English subject for grade XI students at SMA Negeri 1 Mojokerto City. Using a descriptive-qualitative approach, this study observed the implementation process of PjBL as well as students' responses to this method. Data were obtained through interviews and direct observation of students involved in the instructional video-making project. The results showed that the implementation of PjBL not only improved students' understanding of procedure text structure, but also developed additional skills, such as speaking, critical thinking, creativity, and teamwork. Despite challenges in coordination and division of tasks, PjBL succeeded in creating a dynamic and interactive learning environment. The findings confirm that PjBL is an effective strategy in improving the quality of English language learning in senior high schools.